Lessons for cross-species viral transmission surveillance from highly pathogenic avian influenza Korean cat shelter outbreaks - Younjung Kim; Guillaume Fournié; Raphaëlle Métras; Daesub Song; Christl A. Donnelly; Dirk U. Pfeiffer; Pierre Nouvellet (Nature Communications, 2023)
Recent highly pathogenic avian influenza A(H5N1) outbreaks in two Korean cat shelters highlight the need to enhance surveillance for cross-species viral transmission into animal populations kept by humans for non-agricultural or non-conventional livestock farming purposes from a One Health perspective.